PEREMPUAN DALAM GENGGAMAN TEKS: TELAAH ATAS PEMIKIRAN NASR HAMID ABU ZAID DALAMDAWA’RUL KHAUF - Nur (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2013)
This paper wants to examine the Nasher Hamid Abu Zayd thought on the advocacy of women's rights which are summarized in the book Dawa'ir al khauf : qira'ah fil khitab al mar'ah ( a cycle of fear : reading on the women discourse). He said women are still in the shackles of fiqh texts that often discriminated women. The position of women in the domestic space is more valuable and important than the development of creative thinking as demonstrated by the divorce judgment handed down by the religious judge against female lecturer who refused to be pregnant. Starting from this academic anxiety, Abu Zaid build a model of a contextual reading refer to the root tracking of the text. That is, the existence of the text is not a mystery, but a reality storyline. Through a contextual readings, Abu Zaid read two female phenomenon, that is polygamy and inheritance rights. He argues, polygamy is not a tasyri’ problem that is forever, but temporal according to the particular context, as well inheritance rights. First, the Qu'ran ordered give alms to the relatives, the orphans and the poor who do not inherit. Second, the Qu'ran advised that kinship and ethnicity is not a major humanitarian relation, as it has been practiced in the pre-Islamic period. Two basic concepts are used as a foundation to honor women in the problem of inheritance rights.